Grid-tied Multilevel Inverter with Phase-locked Loop Algorithm - Martinez-Montejano, Roberto; Álvarez-Maldonado, Osbaldo-Ulisses; Jaime-Rodríguez, José-Jimmy; González-Badillo, Germánico; Campos-Cantón, Isaac; Martínez-Montejano, Misael-Francisco (Universidad Pedagógica y Tecnológica de Colombia, 2022)
A multilevel inverter is an electronic device capable of changing direct current energy to alternant current energy with a voltage and frequency established by the user. They are ideal for connecting renewable energy sources to the AC grid, energy plants, and smart grids. The voltage must be balanced and synchronized with the electrical network for adequate performance. This paper shows the voltage synchronization between an inverter output voltage and the AC grid using a phase-locked loop based on an adaptive observer. The proposed algorithm can perform under grid uncertainties such as noise and generates a reference signal for the modulation used in the inverter. The algorithm is robust and computationally efficient and can be implemented through basic elements such as operational amplifiers, resistors, and capacitors, reducing its difficulty in executing it in a system.